EMPLOYEE PERFORMANCE IN THE SERVICE OF LAND CERTIFICATES OF THE LAND OFFICE IN BULUKUMBA DISTRICT - Andi Suci Amalia; Andi Cudai Nur; Sulmiah Sulmiah (Universitas Negeri Makassar, 2026)
This research is to find out how employees perform in land certificate services at the bulukumba districk land office. This type of research is descriptive qualitative. Data collection was carried out by means of observation, interviews and documentation. Data analysis uses interactive model analysis, namely data condensation, data presentation and drawing conclusions. The focus of this research is based of mangkunegara theory with five indicators, namely,work quality, work quantity, cooperation, responsibility and initiative. The results of the research show that the performance of employees at the bulukumba district land office in terms of land certificate services is good, in accordance with performance measuring indicators, namely: 1) quality of work is categorized as good, 2) quantity of work is categorized as good, 3) cooperation is categorized as good, 4) responsibility answer is categorized as good, 5) initiative is categorized as good.